تحليل الأخطأ اللغوية في تعليم مهارة الكتابة لدى التلاميذ في المدرسة المتوسطة واحيد هاشم سورابايا: دراسة في ضوء نظرية ستيفن بيت كوردر: Analysis of Linguistic Errors in Teaching Writing Skills to Students at Wahid Hasyim Junior High School, Surabaya: A Study in the Light of Stephen Pit Corder’s Theory - Fashiha Nurin Ni'ami; Mamluatul Hasanah; Faisal; Sahrul Muhamad; Indah Rahmayanti (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2026)
Linguistic errors in Arabic writing pose a serious obstacle for non-native learners in Indonesia, primarily due to grammatical complexity and cross-linguistic differences. This study aims to analyze the types, causes, and solutions for such errors at Madrasah Tsanawiyah Wahid Hasyim Surabaya, employing Stephen Pit Corder's error analysis framework. A qualitative descriptive approach was implemented through observation, interviews, and document analysis of 28 ninth-grade students' writings. Key findings reveal that orthographic errors (e.g., hamzah omission, tanwin mistakes, and letter shape confusion) are most prevalent, followed by syntactic errors (word order and incomplete sentences). The causes include first language interference, weak phonological awareness, limited working memory, and an unsupportive learning environment lacking structured writing practice. This study concludes that errors are not merely failures but rather indicators of learners' internal linguistic system development. It is recommended that teachers design scaffolded instructional strategies, daily writing drills, and utilize visual aids to enhance writing accuracy. تشكل الأخطاء اللغوية في الكتابة باللغة العربية عائقًا خطيرًا أمام المتعلمين من غير الناطقين بها في إندونيسيا، خاصةً بسبب تعقيد القواعد النحوية والاختلافات بين الأنظمة اللغوية. يهدف هذا البحث إلى تحليل أنواع الأخطاء اللغوية في مهارة الكتابة وأسبابها وعلاجاتها المقترحة في المدرسة المتوسطة واحد هاشم سورابايا، بالاعتماد على نظرية تحليل الأخطاء لستيفن بيت كوردر. تم استخدام المنهج النوعي الوصفي من خلال الملاحظة والمقابلة وتحليل الوثائق من نصوص كتابية لـ 28 تلميذة في الصف التاسع. أظهرت النتائج الرئيسية أن الأخطاء الإملائية (مثل نسيان الهمزة، وأخطاء التنوين، وأشكال الحروف) كانت الأكثر شيوعًا، تليها الأخطاء النحوية (كسوء ترتيب الكلمات والجمل غير المكتملة). تعود أسباب هذه الأخطاء إلى تأثير اللغة الأم، وضعف الوعي الصوتي، ومحدودية الذاكرة العاملة، بالإضافة إلى البيئة التعليمية التي لا تدعم الممارسة الكتابية المنظمة بشكل كافٍ. خلص البحث إلى أن الأخطاء اللغوية ليست مجرد إخفاقات، بل هي مؤشرات على تطور النظام اللغوي الداخلي لدى المتعلمات. يوصي البحث بتصميم المعلمات لاستراتيجيات تعليمية متدرجة، وتمارين كتابية يومية، واستخدام وسائل بصرية لتحسين دقة الكتابة.